2020
DOI: 10.3389/fphar.2020.00584
|View full text |Cite
|
Sign up to set email alerts
|

Trilobatin Protects Against Aβ25–35-Induced Hippocampal HT22 Cells Apoptosis Through Mediating ROS/p38/Caspase 3-Dependent Pathway

Abstract: Emerging evidence reveals that an aberrant accumulation of b-amyloid (Ab) is the main reason of Alzheimer's disease (AD) pathogenesis. Thus, inhibition of Ab-induced neurotoxicity may be promising therapeutic tactics to mitigate AD onset and advance. The development of agent candidates by cultured neurons against Ab-induced cytotoxicity is widely accepted to be an efficient strategy to explore the drug for AD patients. Previously, we have revealed that trilobatin (TLB), a small molecule monomer, derives from L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…In the present study, we identified that TLB might alleviate Aβ deposition, Tau pathology, synaptic degeneration, glial In a recent study, Chen et al [26] showed that TLB protects HT22 cell death induced by Aβ 25-35 through the 10…”
Section: Discussionsupporting
confidence: 52%
“…In the present study, we identified that TLB might alleviate Aβ deposition, Tau pathology, synaptic degeneration, glial In a recent study, Chen et al [26] showed that TLB protects HT22 cell death induced by Aβ 25-35 through the 10…”
Section: Discussionsupporting
confidence: 52%
“…Our findings indicate that cortical neurons exposed to Aβ 25-35 , a peptide broadly used in in vitro and in vivo models of AD [ 33 , 34 ], undergo a significant change in the signalling pathways mediated by different mGluRs and ARs, and a reduction in the cell viability. In brief, (i) density of Group I mGluR was increased at the plasma membrane together with an increase in mGluR 1 gene expression; however, the ability of these receptors to activate the PLC system resulted in being impaired.…”
Section: Discussionmentioning
confidence: 91%
“…A similar result was observed in caspase-9 in which GM2 significantly restrained the activation of caspase-9 induced by MPP + ( Figure 3 D). Of note, caspase-3, an eventual protein in the apoptotic cascade that catalyzed the specific cleavage of multiple vital cellular proteins [ 33 ], was also reduced in response to the administration of GM2 in PC12 cells ( Figure 3 C), indicating that GM2 inhibits apoptosis in MPP + -induced PC12 cells.…”
Section: Resultsmentioning
confidence: 99%